Development of metal supported solid oxide fuel cells for operation at 500-600 °c - Brandon,NP; Corcoran,D; Cummins,D; Duckett,A; EI-Khoury,K; Haigh,D; Leah,R; Lewis,G; Maynard,N; McColm,T; Trezona,R; Selcuk,A; et al. (2013)
A novel metal-supported solid oxide fuel cell has been developed that is capable of operating at temperatures of 500-600 °C. The rationale behind the materials used to construct this fuel cell type is given, and results are presented from cell testing on hydrogen and reformed natural gas, including durability trials of some 2500 h duration. This new fuel cell variant is shown to be tolerant of carbon monoxide, durable, robust to thermal and redox cycling, and capable of delivering technologically relevant power densities. © 2013 ASM International.